Pengaruh Kaidah Nahwu terhadap Penentuan Hukum dalam Tafsir QS. Al-Mä'idah [5]: 38 - MAS'UD, INAS (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the determinative influence of Nahwu rules (Arabic grammar) on the process of legal derivation (istinbāṭ) in Islamic jurisprudence, with a case study on the interpretation of Q.S. Al-Mā'idah verse 38 concerning the punishment for theft. Employing a library research method, this research critically examines how syntactic and morphological analyses of key terms—such as "as-sāriq wa as-sāriqah," "aydīhimā," and "faqtha'ū"—form the foundation for differing legal interpretations among scholars. The findings indicate that Nahwu rules serve not only as linguistic verification tools but also as critical mediators that generate legal variations, ranging from textualist-literal to contextualist-maqāṣidī approaches. Differences in interpreting wāw al-'aṭaf, the semantic boundaries of the term "yad," and the implications of fi'il amr are the primary sources of diversity (ikhtilāf) in determining the form and implementation of ḥudūd punishments.